The European Union and the Arctic : a decade into finding its Arcticness - Raspotnik, Andreas; Stepien, Adam (Springer, 2020)
Author's accepted version (postprint). This is an Accepted Manuscript of an article published by Springer in the Frontiers in International Relations book series on 26/06/2020. Available online: https://link.springer.com/chapter/10.1007/978-3-030-45005-2_8 acceptedVersion